Parathyroid carcinoma an unusual endocrine neoplasm: current review - Reyes-Velázquez, Edgar A. (International Journal of Research in Medical Sciences, 2023)
Parathyroid carcinoma is an unusual endocrine neoplasm, in practice, diagnosis and clinical approach is challenging, it could be suspected during pre-surgical approach or in the same surgical procedure, however most of the cases get the diagnosis with histopathology time after surgery, radical surgical approach is the first line treatment of choice, with bloc resection of parathyroid tumor, with the excision of ipsilateral thyroid lobe, cause is unknown, it generally arises as a sporadic disease, although familial cases have been described, most have a painless course, and the most frequent clinical manifestations are due to hypercalcemia secondary to excessive parathyroid hormone secretion by the tumor, on physical examination there is usually nothing evident, mortality is generally due to intractable hypercalcemia rather than to tumor, survival at 5 and 10 years has been reported between 70 to 100% and 50 to 90% respectively.